Autologous haematopoietic stem cell transplantation as a first-line disease-modifying therapy in patients with 'aggressive' multiple sclerosis. (July 2021) - Das, J; Snowden, JA; Burman, J; Freedman, MS; Atkins, H; Bowman, M; Burt, RK; Saccardi, R; Innocenti, C; Mistry, S; Laud, PJ; Jessop, H; et al.
Background: Autologous haematopoietic stem cell transplantation (AHSCT) is an effective treatment for patients with multiple sclerosis (MS) who have highly active disease, despite the use of standard disease-modifying therapies (DMTs). However, the optimal time for offering AHSCT to patients with 'aggressive' MS is yet to be established. Objectives: The objective was to explore the safety and efficacy of AHSCT as a first-line DMT in patients with 'aggressive' MS. Methods: All patients with 'aggressive' MS who received AHSCT as a first-line DMT in five European and North American centres were retrospectively evaluated. Results: Twenty patients were identified. The median interval between diagnosis and AHSCT was 5 (1–20) months. All had multiple poor prognostic markers with a median pre-transplant Expanded Disability Status Scale (EDSS) score of 5.0 (1.5–9.5). After a median follow-up of 30 (12–118) months, the median EDSS score improved to 2.0 (0–6.5, p < 0.0001). No patient had further relapses. Three had residual magnetic resonance imaging (MRI) disease activities in the first 6 months post-transplant, but no further new or enhancing lesions were observed in subsequent scans. Conclusion: AHSCT is safe and effective as a first-line DMT in inducing rapid and sustained remission in patients with 'aggressive' MS.